Perceptions of the IQOS Heated Tobacco Product on Twitter in the United States - Zou, Canruo; Wang, Xueting; Xie, Zidian; Li, Dongmei (Frontiers in Communication, 2021)
After the approval of the sales of IQOS in the United States market, discussions about IQOS have become active on social media. Twitter is a popular social media platform to understand public opinions toward IQOS. This study aims to explore public perceptions toward IQOS on Twitter in the United States. IQOS related tweets from the United States between November 19, 2019 and August 24, 2020 were collected using a Twitter streaming application programming interface (API). Sentiment analysis was performed to determine whether the public perceptions towards IQOS were positive, neutral, or negative. In addition, topics discussed in these tweets were manually coded. From November 2019 to August 2020, the number of tweets discussing IQOS was relatively constant except for a peak starting from July 7, 2020 that lasted for four days. Among IQOS tweets with positive sentiments, the most popular topic is “IQOS is safer than cigarettes”, followed by “IQOS help quit smoking”. Among tweets with negative sentiments, the most popular topic is “illegal marketing/selling to youth”, followed by “health risks/fire hazards”. “FDA approval/regulation” is the most popular topic for tweets with neutral sentiments. After the announcement of the United States Food and Drug Administration (FDA) enforcement policy on unauthorized flavored e-cigarette products on January 2, 2020, the proportion of tweets with positive attitudes toward IQOS significantly increased while the proportion of negative tweets significantly decreased. Our study showed that the public perception of IQOS in the United States became more positive after the FDA enforcement policy on flavored e-cigarettes. While many Twitter users thought IQOS is safer than cigarettes and help quit smoking, some Twitter users complained about the illegal marketing and health risks of IQOS. These findings provide useful information on future tobacco regulation.